Diagnóstico de falhas em máquinas rotativas - Burbano, Christian Eligio Rodríguez (2005)
The dynamic behavior of a cracked shaft was studied both in run-up and run-down transient motion. A mathematical model of the shaft was developed , and experimental tests were performed in order to validate the model. A experimental testing rig was conducted, containing an horizontal flexible rotor with a rigid disc in the mid point between the bearings. Experimental and theo retical responses were compared for both cracked and uncracked shafts. All tests were done for several acceleration rates and unbalance conditions. For the theoretical study of dynamic response of the cracked shaft, the stiffness matrix for a cracked element was deduced, using the modified crack Model of Mayes. The rotor model was obtained by using the finite elements method. The equations of motion were integrated in the time domain by using Newmark method to obtain the transient response. Comparing theoretical and experimental results validated the model. For this purpose, the modified Mayes model was used to represent the dynamic response of the crached shaft. Further simulations were conducted to study the influence of acceleration rates, unbalance amplitude /orientation and crack severity on the response of a cracked shaft, running on transient mo tion.